CAPITAL MISALLOCATION AND FINANCIAL DEVELOPMENT: A SECTOR-LEVEL ANALYSIS - Christian Upper; Daniela Marconi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate the relationship between capital misallocation and financial development in six countries at different levels of development. We find that more developed financial systems perform better at allocating capital investment. If financial development is low, faster capital accumulation results in a worsening of allocative efficiency. This effect reverses for higher levels of financial development. Sectors with high R&D expenditures or high capital investment benefit most.
Keywords: O47; O16; 330